Managing IT innovation: a study of information technology implementations in Malaysian banks - Ahlan, Abdul Rahman (ProQuest LLC 2013, 2005)
Technology plays an important role in organization's innovation activities and the financial services sector is one of the major adopters of technology innovations. In Malaysia computers began to be introduced in the financial services institutions only in the 1980s. Today, the deployment of computer technology has gone far beyond automating manual banking operations in the back office. Indeed most of the products and services offered by the banking institutions could only be possible through the exploitation of information technology (IT). There is limited research in the area of technology innovation in Malaysia. Most of the existing innovation researches are related to industrial innovation. Wider perspective innovation research covering different industries is scarce, particularly in Malaysian banking industry - implying the infancy stage of research in this area. There is still very much to be researched and learned in order to understand the nature of technology innovation in the Malaysian banking industry specifically in the area of IT implementations. The current research attempts to understand this aspect in the context of Malaysian banking organizations. Using qualitative technique, twelve case study banks were analysed. Data Reduction Process and Thematic data analysis generated three distinguished themes - strategy, structure, an d technology. Evidence from the findings suggests these themes are factors that have impact on the IT system implementations in the Malaysian banks. The nature and interaction of these factors were found to affect the IT system implementations in the way that would facilitate or impede the implementation process. This research concludes that the evidence and findings produced positively corresponds to the established theoretical perspectives and frameworks produced by studies in the same area in the West. These findings suggest that those perspectives and frameworks are highly applicable in the Malaysian context.